Application of the Singing Method to Increase Student Learning Motivation in Class 5 Science Subjects 6 Themes Heat and Transfer at SDN 20 Banda Aceh - Juliani, Juliani; Fitri, Aida; Ahadin, Ahadin (Universitas Syiah Kuala, 2023)
The purpose of this research is to analyze the problem of how to apply the singing method to increase students' learning motivation in science subject class 5 theme 6 heat and its transfer at SD N 20 Banda Aceh. Efforts were made to solve the problem of students' lack of learning motivation by using the singing method. The approach taken for this research is qualitative with descriptive research type. Class V SD Negeri 20 Banda Aceh totaling 26 people as subjects in this research with data collection techniques in the form of questionnaires. The results of the study obtained that the average score of the questionnaire achieved by students was 3.53, then after the singing method was applied, the average value achieved was categorized as high. It was then the authors concluded that the application of the singing method was able to support increasing student learning motivation in science subjects grade 5 theme 6 heat and its transfer to SD N 20 Banda Aceh was able to increase student learning motivation at SD N 20 Banda Aceh.